2008
DOI: 10.1042/bj20071469
|View full text |Cite
|
Sign up to set email alerts
|

VLDL exits from the endoplasmic reticulum in a specialized vesicle, the VLDL transport vesicle, in rat primary hepatocytes

Abstract: The movement of VLDL [very-LDL (low-density lipoprotein)] from the ER (endoplasmic reticulum) to the Golgi is required for its eventual secretion from hepatocytes and represents a potential target in controlling elevated concentrations of its metabolite LDL, the major determinant of atherosclerosis. To study this process, an in vitro ER-budding assay was developed to examine the generation of the VTV (VLDL transport vesicle) and PTV (protein transport vesicles) using ER isolated from [(14)C]TAG (triacylglycero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
163
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(178 citation statements)
references
References 47 publications
13
163
2
Order By: Relevance
“…The occurrence of VLDL-associated viral particles (lipoviroparticles) in patient sera further strengthen the notion that HCV and VLDL secretion overlap and that HCV co-opts the VLDL secretory pathway for its secretion (50). Although the intricate details of VLDL biogenesis are still unclear, it is well known that the VLDL particles traffic through the Golgi compartments, implicating a similar pathway for HCV virion egress (19,51).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The occurrence of VLDL-associated viral particles (lipoviroparticles) in patient sera further strengthen the notion that HCV and VLDL secretion overlap and that HCV co-opts the VLDL secretory pathway for its secretion (50). Although the intricate details of VLDL biogenesis are still unclear, it is well known that the VLDL particles traffic through the Golgi compartments, implicating a similar pathway for HCV virion egress (19,51).…”
Section: Discussionmentioning
confidence: 71%
“…These * This work was supported, in whole or in part, by National Institutes of Health pre-VLDL particles are subjected to additional lipidation to generate a mature VLDL particle. Although the mechanism and location of this second lipidation event is not clear, it is understood that the VLDL particles are transported from the ER to the Golgi in specialized vesicles (VLDL transport vesicles) and are eventually secreted via the Golgi secretory pathway (19). It has been shown that perturbation of VLDL biogenesis inhibits HCV virion secretion (3,11,12).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…166 Mature VLDL is transported to the Golgi and finally secreted. 163 By using mass spectrometry analyses of affinity purified HCV particles produced in cell culture, it was found that the lipid ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Discussionmentioning
confidence: 99%
“…LDs and luLDs are important for the transfer of TGs to VLDL2. 163 They are composed of a core of neutral lipids and surrounded by a monolayer lipid membrane. Although LDs and luLDs share a very similar lipid composition, they are decorated with different sets of proteins, regulating their size, mobility and localization: 152 ADRP and the 47 kDa tail interacting protein (TIP47) are found on the surface of LDs, whereas MTP, ApoE and TG hydrolase cofractionate with luLDs, but not with LDs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, chylomicrons are transported on unique particles, different from those used for protein transport, by intestinal cells. Similarly, unique particles have been shown to transport hepatic lipoproteins in the liver (164).…”
Section: Assembly Secretion and Regulation Of Intestinal Lipoproteinsmentioning
confidence: 99%